Rentabilidad Y Sostenibilidad Económica, Ambiental Y Social En Áreas Protegidas Aseguradas A Través Del Modelo De Gestión Estudio De Caso: Refugios Carrel YWhymper Reserva Chimborazo - Guadalupe, Carla Sofía Arguello; Ortega, Luis Rafael Fiallos; Chinchuela, María Flor; Moyota, Paulina Beatriz Díaz; Bernal, Catalina Margarita Verdugo; Santillan, Carlos Arturo Jara; Piray, Miryan Isabel Quezada (European Scientific Journal, ESJ, 2017)
This research is aimed to evaluate the management model for the operation of the shelters Carrel and Whymper within La Reserva de Produccion de Fauna Chimborazo (RPFCH – acronym in Spanish for this protected area) through the design and implementation of an evaluation matrix. This matrix tool is specifically designed to evaluate management models and operations of tourist services in protected areas. The model integrates three criteria that have to do with social, economic and environmental sustainability. The matrix has been designed based on four components: 1) The sustainability indicators created by the Economic Commission for Latin America and the Caribbean (CEPAL – acronym in Spanish), 2) A corporate social responsibility approach, 3) The global criteria of sustainable tourism and 4) A guide to good practices of sustainable tourism. These matrix components were adapted to the conditions of the tourist services offered at the Carrel and Whymper shelters. The evaluation detected that the current management model meets only 40% of the evaluation indicators sustainability criteria, which demonstrates a poor sustainability model. Based on this review, a new management approach is suggested under the eco-efficient shelters model. This ensures that the investors not only reach economic profitability, but also they obtain longterm environmental and social sustainability. This model not only establishes parameters that allow for investors to make the appropriate economic and management decisions, but also establishes policies that ensure the conservation of protected areas